Mathematical modelling of running crown forest fires - Barovik, Dmitry; Taranchuk, Valery (Mathematical Modelling and Analysis, 2010)
Adapted mathematical model for simulation of running crown forest fire propagation is considered. Simplifying assumptions, equations of the model, initial and boundary conditions, finite difference approximations are introduced. The results of computer modelling and the peculiarities of forest fire behaviour in heterogeneous forests are discussed.First published online: 09 Jun 2011